Reformulation of Patent Law in Indonesia Regarding Patent Waiver of Vaccines in Certain Circumstances - Serafim, Gladysta Viola; Kusumadara, Afifah; Widyanti, Yenny Eta (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This research aims to reformulate patent law in Indonesia based on the 12th WTO MC Decision on the TRIPs Agreement related to patent waivers for vaccines in certain circumstances, such as pandemics. Patenting vaccines during a pandemic can hamper efforts to handle the pandemic quickly and effectively and make access to vaccines limited, especially for lower-middle-income countries (LMICs). This can be seen in the implementation of Covid-19 vaccination where there is a gap in vaccination rates and vaccine prices between developed countries and LMICs countries. For example, vaccine supplies in Indonesia as one of the LMICs countries could only meet 24% of the coverage target of 181 million people at the beginning of the Covid-19 pandemic. The patent law in Indonesia has provided flexibility regarding the implementation of patents for vaccines in certain circumstances through the implementation of patents by the government, but in fact it still cannot overcome the scarcity of vaccines in an emergency in Indonesia. This study uses normative (doctrinal) research types with statue, conceptual, and analytical. Based on the results of the research, in order to minimize existing problems so that they do not occur in the future, Indonesia can reformulate the formulation of patent laws in Indonesia based on the TRIPs Agreement, namely first, the regulation that the implementation of patent waivers for vaccines in certain circumstances does not require permission from the patent holder; second, the regulation on determining the amount of remuneration for inventors; and third, regulation on the prohibition of re-export of vaccines whose patents are ignored.